Kemampuan dan Dukungan: Meninjau Orientasi Masa Depan Santri Berdasarkan Adversity Quotient dan Dukungan Sosial - Husain Ali Assyafii; Lusi Nuryanti (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2023)
Previous studies show that Indonesian teenagers tend to have a low level of future orientation, which has an impact on increasing unemployment rates. There are still few studies on future orientation carried out on students who have different challenges and living conditions compared to other teenagers. This research aims to empirically examine the relationship between adversity quotient and social support on students' future orientation. This research used quantitative correlational methods with the total participants of 223 Aliyah students (high school equivalent) at the Ta'mirul Islam Islamic Boarding School, Surakarta. The results of multiple regression analysis show that there is a significant positive relationship between adversity quotient and social support on students' future orientation (F= 95.654, sig= .00) with an effective contribution of 45.1%. The categorization results show that the majority of students have a very high future orientation, 44.4%.